The Influence Of Work Experience, Work Environment, And Work Culture Through Motivation On Employee Performance At PT. Ekamas Fortuna Malang - Agus Bambang Sunyoto; Agung Winarno; Sopiah (PT. Maju Malaqbi Makkarana, 2026)
This study aims to examine work experience, work environment, and work culture on employee performance, both directly and through work motivation as a mediating variable. This research is based on two main grand theories, namely Maslow's Hierarchy of Needs and Self-Determination Theory. Quantitative approach with survey method, The research population is all employees of the production division of PT Ekamas Fortuna Malang which totals 332 people. Sampling was carried out using the proportionate stratified random sampling technique with a sample of 179 respondents. Data analysis was carried out using the Structural Equation Modeling method based on Partial Least Square (SEM-PLS) with the help of SmartPLS software. The results of the hypothesis testing showed that all ten hypotheses proposed in this study were proven to be statistically supported. Work experience, work environment, and work culture were each proven to have a positive and significant effect on employee work motivation, indicating that these three factors are relevant motivational antecedents in the context of the manufacturing industry and motivation has also been shown to mediate the relationship between these three variables. An important finding of this study is the confirmation of the dual role of work motivation, namely as a variable that directly drives employee performance as well as as a mediator that strengthens and channels the indirect influence of work experience, work environment, and work culture on performance.